Peranan KH. Abdullah Zawawi Izhom dalam Penyebaran Islam di Palembang - Padila, Padila (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2018)
In this paper examines how the role of KH. Abdullah Zawawi Izhom in the distribution of Islam in Palembang. The study in this paper discussed Â theÂ history of KH Abdullah Zawawi Izhomâ€™s role in the distribution of Islam in Palembang, from 1930 until 2013. Many others are studying about the great scholars and well known in the public, on the other hand if in further study the role of KH. Abdullah Zawawi Izhom in accessing Islam is also quite significant, and so far there has been no research that discussed about his role in the spread of Islam in Palembang.Researchers are very important to examine how the role of KH. Abdullah Zawawi Izhom in the spread of Islam in Palembang, because there are several reasons that make this research is interesting. The first is about KH figure. Abdullah Zawawi Izhom as a local cleric who is very active in spreading Islam in Palembang and so far there is no significant discussion about him. Second, is how the history of his struggle in introducing an era in various islam. Based on the argument, the big question in this research is how the role of KH. Abdullah Zawawi Izhom in the distributing of Islam in Palembang. In order to process the data obtained from the optimal results, in this study using role theory. In this study the authors use the historical method that aims to collect, evaluate and reveal facts to enforce facts and strong evidence. The findings of this study is K. H Abdullah Zawawi Izhom, one of the important figures in the spread of Islam in the city of Palembang with various evidence, such as relics of mosques and majlis ta'lim who is still active nowadays. Then in the form of dakwah that he did, he was directed to the informal targets, such as inter-mosque da'wah, musholla, or ta'lim assembly. He also bought more Muslims to the impelementation in daily life. Then to further disseminate the science he had, he printed some students to spread around Palembang to keep in distributing Islam